2019
DOI: 10.1007/s10488-019-00927-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Supervisory Support on Turnover Intention: The Mediating Role of Burnout and Job Satisfaction in a Longitudinal Study

Abstract: High rates of provider turnover are problematic for our mental health system. Research indicates that supervisory support could alleviate some turnover intention by decreasing emotional exhaustion (a key component of burnout) as well as by increasing job satisfaction. However, the potential mediation mechanisms have not been rigorously tested. Longitudinal data collected from 195 direct clinical care providers at two community mental health centers identified positive effects of supervisory support on reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 80 publications
0
47
0
5
Order By: Relevance
“…Previous studies have demonstrated that higher levels of turnover intention were associated with lower levels of job satisfaction. 3,[24][25][26][27] This finding suggests that an improvement in job satisfaction could serve as an effective way to prevent or minimize burnout and provide new insight for future studies on ways to improve job satisfaction of GPs while indirectly addressing high turnover problems.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have demonstrated that higher levels of turnover intention were associated with lower levels of job satisfaction. 3,[24][25][26][27] This finding suggests that an improvement in job satisfaction could serve as an effective way to prevent or minimize burnout and provide new insight for future studies on ways to improve job satisfaction of GPs while indirectly addressing high turnover problems.…”
Section: Discussionmentioning
confidence: 91%
“…The two dimensions of job burnout (except DP) and perceived social support were negatively correlated, partially confirming H4. Barnett et al (2019) found workplace social support, not personal social support, was associated with lower psychological distress; Sadaaki Fukui found (Fukui et al, 2019) that supervisory support had positive effects in reducing turnover intention through reduced EE. The study indicated that in the workplace the support from supervisors and colleagues was more important than that of family and friends (Fukui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Barnett et al (2019) found workplace social support, not personal social support, was associated with lower psychological distress; Sadaaki Fukui found (Fukui et al, 2019) that supervisory support had positive effects in reducing turnover intention through reduced EE. The study indicated that in the workplace the support from supervisors and colleagues was more important than that of family and friends (Fukui et al, 2019). We found no significant correlation between DP and perceived social support, but LPA and perceived social support were significantly correlated, and FAS, FRS, and OS were all related to female doctors' LPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations